Administrative Law Enforcement through Supervision Instruments on Brantas River Pollution - Eduardo Saratoga Wrahatnala; Suparto Wijoyo; Radian Salman; Rosa Ristawati (Budapest International Research and Critics University, 2021)
The Brantas River, which is a national strategic area, is currently experiencing pollution. The massive pollution of the Brantas River and causing its water quality to decline is a problem that must be taken seriously. The worrying quality of the Brantas River shows the performance of the Indonesian government at the central, provincial, and district/city levels in managing river quality. Although there has been a Supreme Court decision regarding the pollution of the Brantas River, the government does not yet have a comprehensive plan and serious political will to restore the polluted Brantas River. This paper aims to analyze the enforcement of environmental administrative law through monitoring instruments as the implications of a lawsuit for pollution of the Brantas River based on the Supreme Court of the Republic of Indonesia Decision No. 08/Pdt.G/2019/PNSb. Based on the results of the analysis, it is necessary to take concrete actions from executive institutions and the community so that the pollution of the Brantas River is immediately resolved and does not recur in the future and so that the water quality can improve better.